Diagnostic Evaluation Of Lecturer Quality In Learning Process At New Private Higher Education Institutions In Tangerang, Indonesia - Sasmoko; Trilaksono, Teddy; Indrianti, Yasinta; Ahmad, Roslee Bin (American Scientific Publishers, 2024)
Volume 22, Numbers 5-6